(untitled) (Fiep Bulletin - online, 2015)
The Down Syndrome (DS) is a genetic disorder with specific phenotypic characteristics, these characteristics along with their sufferers have low basal metabolism which is related to the onset of obesity and chronic diseases such as diabetes, heart disease, dyslipidemia. The objective of this paper is to show through the literature review, such as changing eating habits of patients with SD is directly related to improved quality of life, since obesity and these chronic non-communicable diseases that affect can be treated or prevented with feeding. Theoretical foundation for the scientific articles, theses and dissertations on those with SD and Nutrition Education as aspect of improving quality of life were used. Before these appointments, it is necessary that healthy eating habits are present from childhood for people with Down syndrome, because while encouraging proper intake of food, nutrition becomes important in improving the quality of life of these people.